Ideal Physical Profile of Water Ski and Wakeboard Athletes: A Case Study of Dki Jakarta's Preparation for PON XXI Aceh-North Sumatra 2024 - Maslikah, Uzizatun; Fachrezzy, Fahmy; Hermawan, Iwan; Ali, Masnur; Jariono, Gatot; Nurhidayat, Nurhidayat (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2025)
This study aims to identify the ideal physical profile of water ski and wakeboard athletes in the preparation of the DKI Jakarta contingent to face the XXI Aceh-North Sumatra National Sports Week (PON) 2024. Water ski and wakeboarding are water sports that require a combination of physical strength, endurance, flexibility, and agility to support optimal performance. Therefore, understanding the ideal physical components is very important in supporting the success of athletes in national competitions. This study uses a quantitative descriptive method involving 20 water ski and wakeboard athletes from DKI Jakarta. Physical measurements were carried out using standardized instruments, including anthropometric measurements (height, weight, BMI, chest circumference, waist, and body fat percentage), muscle strength (dynamometer and push up), cardiovascular endurance (Cooper test), flexibility (sit and reach test), and speed and agility (shuttle run and 30-meter sprint). The data obtained were analyzed descriptively to determine the mean, standard deviation, and distribution of each physical component measured. The results show that water skiers and wakeboards have a distinctive physical profile, where arm and leg muscle strength, good cardiovascular endurance, and high flexibility are the main factors that support their performance. The average BMI of athletes is in the ideal category, with a low percentage of body fat. Flexibility and speed are also important components that play a role in the success of athletes when maneuvering on water.